Pain and self-rated health among middle-aged and older Canadians: an analysis of the Canadian community health survey-healthy aging - Batholomew Chireh; Carl D'Arcy (BMC, 2018)
Abstract Background Pain is an important health problem adversely affecting functionality and quality of life. Though self- rated health (SRH) is a major predictor of mortality, its relationship with pain is not well understood. We explore 1) how pain and age interact to influence SRH, and 2) provincial variations in SRH across Canada. Methods We analyzed cross-sectional data from Statistics Canada's Canadian Community Health Survey-Healthy Aging (n = 30,685), which targeted those 45 years and older and was conducted from 2008 to 12-01 to 2009-11-30. The response rate was 74.4%.The topics covered included socio-demographics, well-being and chronic diseases. We performed both bivariate and multivariate analyses between each predictor and SRH; unadjusted and adjusted odds ratios and 95% confidence intervals are reported. Two-level logistic regression mixed model was used to account for provincial differences. An intraclass correlation coefficient was also computed. Results Slightly more than half of respondents (56.40%) were female. In bivariate analyses, those experiencing pain had an odds ratio of 0.20. Which means that the odds of reporting good self-rated health are 4 to 5 times lower for those with pain, compare to the odds of reporting good self-rated health among those without pain (p < 0.001). In multivariate analyses the highly educated, female gender, the never married or single and households with high yearly income were predictors of good health (p < 0.001). Those who reported depressive symptoms, the lonely, the obese, daily smokers and/or the stressed were less likely to rate their health as good (p < 0.001). The influence of pain on SRH was stronger among younger age groups (45-54 years) compared to older age groups (75-84 years, with an odds ratio of 3.53 [p < 0.001] versus 3.14 [p < 0.001]). Conclusions Pain, among other determinants, is associated with SRH. Individuals in rating their health may consider a variety of factors, some of which may not be apparent to health providers. We found that those who reported depressive symptoms, were daily smokers, the obese, the lonely, and/or having a stressful life were less likely to rate their health as good. No significant provincial variations in SRH in Canada was observed in this study.